Morphological and physiological responses of two species of Capsicum (Capsicum annuum L. and Capsicum chinense Jacq.) under conditions of water deficit - Fernández-Zambrano, Luis F.; Corozo Quiñonez, Liliana; Monteros Altamirano, Álvaro; Arteaga Alcívar, Francisco; Jaimez, Ramón E. (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
Drought and water scarcity, effects from ongoing climate change, are between main limitations in agricultural production. In this sense, this study aimed to compare the differences morphological and physiological responses between local cultivars of Capsicum annuum L. and Capsicum chinense Jacq under WD conditions. After 20 days of being transplanted and maintained with adequate irrigation and fertilization, in a randomized block design, plants of four local cultivars (2 of C. annuum and 2 of C. chinense) were subjected to two treatments: WD consisting of 14 days without irrigation, and plants watered every three days. The relative water content (RWC), root volume, leaf area, specific leaf area, dry weight of the different organs and leaf nitrogen concentration were measured. The results show that, under conditions of WD, plants of C. annuum and C. chinense decreases significantly leaf RWC, root volumes, total growth and leaf nitrogen concentration. In the case of C. annuum, the WD affected production, which varied between cultivars. It seems that the mobilization of photoassimilates towards fruits is a strategy for a higher production for some cultivar of C. annuum as demonstrated in the cultivar ECU-2254b, however, it was the cultivar that showed the lowest RWC in both conditions of water availability. The cultivar of C. chinense ECU-2241, showed a better tolerance to WD presenting greater root growth and greater RWC.